Some Aspects of Renewable Energy Development in the Arctic Zone of the Russian Federation - T. S. Gabderakhmanova; S. V. Kiseleva; O. S. Popel; A. B. Tarasenko; Т. С. Габдерахманова; С. В. Киселева; О. С. Попель; А. Б. Тарасенко (Alternative Energy and Ecology (ISJAEE), 2016)
The article discusses the features of renewable energy development in the Arctic Zone of the Russian Federation and gives the results of the resource assessments as well as gross and technical potential assessments of solar, wind and waste of timber industry in the Russian Arctic. Maps of solar and wind resource distribution allow the researchers to reveal the most promising regions for renewable energy development.Moreover, the article analyzes the power consumption structure of energy consumers in the region. The authors of this article prepare a database of existing and planned power plants based on renewable energy sources in the Russian Arctic that allows estimating the volume of installed capacity, the type of used renewable energy sources and the fuel substitution degree.The maps which are built on the investigation results are included into the GIS Renewable Energy Sources of the Russian Federation. They may be used as a convenient tool for preliminary assessments of solar and wind energy potentials, possibility and of energy system based on renewable energy.The article gives some requirements for construction of PV systems in the region and shows the operation features of different types of electric energy storages which were found during experiments. The features should be taken into account for design of power plants based on renewable energy sources in the region. В работе рассмотрены особенности развития возобновляемой энергетики в Арктической зоне Российской Федерации (АЗРФ).Приведены результаты оценок ресурсов, а также валового и технического потенциала энергии солнца, ветра и отходов лесной и деревообрабатывающей промышленности на территории АЗРФ. Детальные карты распределения ресурсов солнца и ветра позволяют выявить перспективные для внедрения возобновляемой энергетики регионы.Проанализирована структура и диапазоны потребляемой мощности потенциальных потребителей от автономных источников энергии в регионе. Подготовлена база данных действующих и проектируемых объектов на основе ВИЭ в АЗРФ, ...